2015
DOI: 10.1016/j.jcrs.2014.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and topographic effects of single-segment intrastromal corneal ring segments in eyes with moderate to severe keratoconus and inferior cones

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Several studies have reported that INTACS is effective in keratoconus 1420 . Uncorrected distance visual acuity and spherical equivalent can be improved after INTACS implantation 1420 . However, these reports mainly focused on short-term (less than one year) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that INTACS is effective in keratoconus 1420 . Uncorrected distance visual acuity and spherical equivalent can be improved after INTACS implantation 1420 . However, these reports mainly focused on short-term (less than one year) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1). Removal of duplicates and use of the selection criteria reduced the number of articles reporting the evaluation of ICRS in keratoconus to 95 articles 8,1416,26…”
Section: Resultsmentioning
confidence: 99%
“…The reference point was a Sinskey hook marking the center of the pupil. Channel depth varied between 70% ( references 1416, 33, 35, 37, 48-54, 63, 65, 66, 70, 80, 82, 83, 87, 88, 90, 92, 95, 98, 99, 102, 103, 105, 108, 109, 111, 113, 114 ), 75% ( references 26, 27, 34, 39, 41, 42, 45, 58, 60, 64, 71, 79, 110 ), or 80% ( references 8, 29, 30, 32, 33, 43, 47, 5456, 59, 62, 6769, 72–…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moderate anatomical abnormality with structural instability (i.e., keratoconus, keratoglobus, pellucid marginal degeneration, or LASIK ectasia), prescription inserts (Intacs, Addition Technology) can be used in an intelligently-applied, asymmetric fashion using different ring combinations (i.e., 0.45 and 0.3), superficial and deep placement, single and paired rings, and incision placement manipulation. 9 The inserts then act as braces in this unstable cornea, first to correct the progress of the abnormality, and second-in a case-specific, customized fashion-to visually focus the rehabilitated cornea and further present it for laser vision surgery to correct astigmatism, which is the most common error with keratoconus that removes the least amount of tissue with the excimer laser. Ocular surface pathologies-such as advanced pterygium, recurrent pterygium, limbal lesions-can be addressed with amniotic membrane reconstruction to clear the pathology on the cornea and rehabilitate the ocular surface to present the cornea for vision corrective surgery once again.…”
Section: Gulani Corneal Scar Classificationmentioning
confidence: 99%